A platform for interoperable fusion models - Royer, V.; Challine, J.-F. (FUSION 2000 : proceedings of the Third International Conference on Information Fusion : July 10-13, 2000, Cité des Sciences et de l'Industrie, Paris, France, 2000)
The paper presents a generic and extensible prototype platform for intelligence fusion. High level semantics data are processed. The fusion process is designed as an heterogeneous "algebra" of fusion operations. Each fusion operation works on given abstract data types. They are generic, being independent of the semantics of data. Data and knowledge semantics is given explicitly by an input ontology together with descriptive models of the ontology concepts. The models are automatically encoded into representations suitable for the fusion operations. The approach allows us to integrate external fusion algorithms, as well as to change the underlying ontology. Interoperability is a consequence of the ontology based approach: the consistent combination of fusion operations is indeed made possible because of a common semantics of data and common reference concepts, not because of common data and knowledge.